2021
DOI: 10.33899/ijvs.2021.129420.1646
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological and therapeutic study of Sarcoptes scabiei parasite in cows of Anbar province, Iraq

Abstract: This study was conducted to determine the prevalence of Sarcoptes scabiei infection in cows in Anbar province, Iraq. The parasite was diagnosed in the laboratory via examining skin scrapings taken from the suspected cows. The results indicated that the infection rate in cows with S. scabiei reached 37.5%, the animals of 3 months -<3 years old have the highest rate of infection. The results of the study showed that head lesions were more present and clearer than others. Furthermore, the highest rate of infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
(23 reference statements)
3
2
1
Order By: Relevance
“…These dif- ferences could be attributed to the number of animals examined and the management's performance. On the other hand, our results agreed with Shahatha et al (2022), who reported that the infestation rate with S. scabiei in cows was 37.5%. The most frequent lesions in rabbits were hyperkeratosis on the head and ears (26.8%), then the abdomen and back (57.1%), and finally on the legs (44.6%), while the alopecia came in the second place after hyperkeratosis and its rates are 26.8% on the head and ears, 57.1% on the abdomen and back, and 19.6% on the tail and perineal areas.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These dif- ferences could be attributed to the number of animals examined and the management's performance. On the other hand, our results agreed with Shahatha et al (2022), who reported that the infestation rate with S. scabiei in cows was 37.5%. The most frequent lesions in rabbits were hyperkeratosis on the head and ears (26.8%), then the abdomen and back (57.1%), and finally on the legs (44.6%), while the alopecia came in the second place after hyperkeratosis and its rates are 26.8% on the head and ears, 57.1% on the abdomen and back, and 19.6% on the tail and perineal areas.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study clarified that the percentage of infestation with S. scabiei var. cuniculi was 38.5%, which was too close to the infestation rate with the same mite on sheep (34.6%) and on rabbits (41.6%) as reported by Shahatha et al (2022) whereas the infestation rate with Psoroptes cuniculi, N. cati var. cuniculi, D. cuniculi and finally Cheyletiella spp.…”
Section: Discussioncontrasting
confidence: 51%
“…cameli in Pakistan, recording 42.22% (27). Most recently, this parasite is also found in cows of Anbar province, Iraq, recording 37.5% which tends to be in agreement with the present study (28). However, the current percentage is high compared to a previous study which are carried out in three governorates; Al-Qadissiya, Al-Najaf and Al-Muthanna in Iraq (29) and Saudi Arabian camels (30).…”
Section: Discussionsupporting
confidence: 91%
“…The effectiveness of the alcoholic extract in inhibiting the growth of the L. donovani parasites is attributed to the fact that it contains many active substances such as alkaloids, flavonoids, glycosides, sterols, and volatile oils that make the cell membrane completely permeable, which leads to the entry of some substances that cause toxicity cytotoxic or the merging of the entering materials with other substances inside the cells, which leads to the disruption of their work or turning them into harmful substances causing the parasite to die or it may affect the parasite's cell membrane, causing it to necrosis [20]. Alkaloids also inhibit the work of the topoisomerase enzyme, which participates in the various vital activities of the parasite, including the process of DNA replication and thus stopping the physiological activities and the parasite's destruction [21], [22]. In addition to inhibiting the activity of Acetylcholinesterase enzyme (AchE), which prevents the passage of ions through the cell membrane and affects the vital activities of the parasite, thus causing cell breakdown and parasite death [23], [24].…”
Section: Resultsmentioning
confidence: 99%